AUTHENTIC EMERGENCE OF FLEXIBILITY IN CONTEMPORARY ARCHITECTURE. - Farjami, Ghazal (Open House Int, 2015)
Flexibility is known as an important term in the field of open buildings especially during modern era. Idea of flexibility has been one of the prominent implications in traditional Iranian architecture emerged in spatial organizations. Although, during modern period this quality of spaces has been mostly ignored some of the contemporary architects attempted to reconsider this characteristic in their projects. However, providing an interview with 7pioneering contemporary Iranian architects and visiting their 25 residential projects it seems that flexibility has been reinterpreted in some of their projects. This research is an attempt for examining the idea of flexibility in 6projects of 3of these architects who were obsessed with this spatial term in their architectural works. Based on the architect's words and analysis of their projects, and also looking for the roots of flexibility in traditional architecture, it can be asserted that there is an authentic emergence of flexibility in these projects. Examining these projects according to three main indicators of flexibility in modern architecture as structural systems, service organization and architectural layout, it is also tried to find their relation with traditional architecture. Being adapted with new lifestyles while ingrained in cultural and environmental issues of its context, idea of flexibility employed as an authentic characteristic of spatial configuration in some of the contemporary buildings in Iran.
Keywords: Flexibility; Residential Buildings; Contemporary Iranian Architecture; Traditional Architecture; Authenticity